About some Lithuanian state-level maturity examination problems in mathematics - Karikovas, Erikas (Lietuvos matematikos rinkinys, 2022)
The article makes observations on some of the problems in the first part of the 2014–2022 state-level maturity examination in Lithuania. It discusses solutions to such problems without and with a calculator. These observations are intended to draw attention to the problems in the test. The article aims to show that such problems do not fulfil the function of the exam – to test students’ knowledge.